METHOD FOR IDENTIFICATION OF SIGNALS: METHOD FOR IDENTIFICATION OF SIGNALS - Zhekov, Zhivko; Antonov, Anton; Boyanov, Petar; Chervenkov, Dimitar; Trifonov , Tihomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper to the research of particular objects from optic spectrum by means of optical-electronic devices is related. A mathematical model for identification of signals with two degrees of freedom is proposed. Object of research is a variant of discrete signal processing in the temporary area.